Influence of Mechanical Environment on Limbal and Corneal Epithelial Cells - Masterton, Sophia (Trinity College Dublin. School of Engineering. Discipline of Mechanical & Manuf. Eng, 2021)
Corneal blindness is the 4th leading cause of blindness and the most transplanted tissue worldwide. Severe donor shortages and immune rejection has led to research into alternative therapies for corneal transplantation. This thesis focused on the outermost layer of the cornea; the corneal epithelium. Stem cells located at the corneal periphery replenish this epithelial layer; loss of this function may be restored by expanding these cells ex vivo followed by transplantation. The role of the corneal epithelial cells physical environment was studied with the aim of improving expansion techniques for these cells. The first study examined the media used for expanding a corneal epithelial cell line was optimised to retain expression of stem cell characteristics. This study concluded that a high glucose high calcium media formulation should not be used when culturing these cells. Next, the effect of substrate stiffness was examined which showed that substrates in the range of 10 105kPa were most suited to corneal epithelial expansion, while higher stiffness s promoted proliferative phenotypes. Following this, shear stress from fluid flow was studied which showed that human LESCs exposed to 1 day low shear stress significantly enhanced stem cell characteristics. After 3 days under shear conditions, a more stratified epithelial layer appeared with increased expression of ZO-1 and a more in vivo orientation of cells were observed. TRPV4, a mechanosensitive ion channel implicated in shear stress was significantly upregulated in both shear conditions. This suggested that this pathway is implicated in the corneal epithelium s shear stress response and may be a therapeutic target for mimicking this response in vitro, removing the need for shear which led to the next study of this thesis. TRPV4 was pharmacologically activated or inhibited and cultured for 2 days. Results showed that inhibition of this channel increased stem cell marker expression, similar to results observed under shear stress. Finally, both substrate stiffness and shear stress was combined to determine if these two mechanical stimuli produced a synergistic or opposing effect. It was shown that a stiffer substrate in combination with flow significantly enhanced stem cell marker expression suggesting that a synergistic relationship exists between these two stimuli. To conclude, this thesis identified an optimum stiffness range to culture corneal epithelial cells which may be applied in biomaterial design and culture environments. This work also provided insight into the regulatory mechanism of the corneal epithelial shear stress response. This response was successfully mimicked while also identifying a potential drug target for topical therapy and improving ex vivo expansion of LSCs before transplantation; removing the need for a fluid flow bioreactor. Furthermore, combination of both stiffness and shear showed a synergistic relationship which may be used to improve or mimic culture environments of the corneal epithelium. Overall, this thesis has provided novel insight into our understanding of the corneal epithelium while providing several optimisations of culturing environments for corneal epithelial cells. This work may aid in increased transplant success and decrease donor shortages worldwide. .
APPROVED
Keywords: Cornea; Epithelium; Mechanical Environment